2001
DOI: 10.1007/s001060050761
|View full text |Cite
|
Sign up to set email alerts
|

Verarbeitung vestibulärer Impulse im Zentralnervensystem

Abstract: We are the first to point out the functional connection between the hippocampus and the vestibular system in this report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2003
2003

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Scientists relying on this technique have made efforts to guarantee experimental conditions under which the tactile, nociceptive, and possibly auditory components of CVS do not influence the results of the measurements, i.e., waiting for 10 s after the injection of cold water prior to the start of PET data acquisition (Bottini et al 1994(Bottini et al , 2001 or delaying the start of PET investigations by an average of 145 and 25 s following stimulation with cold water or warm air, respectively, in an effort ensure that the effect of fast-quenching activation due to mechanical and CVS is decreased (Wenzel et al 1996). In earlier experiments (Kisely et al 2001), we applied the technique of stimulation with icy water and found that this resulted in an expressed and prolonged sensation of cold and pain, which persisted during data acquisition. These observations immediately led to the question as to which of the components of the changes in rCBF induced by CVS stimulation could be attributed to the processing of vestibular signals and which were related to the pain or cold sensation.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Scientists relying on this technique have made efforts to guarantee experimental conditions under which the tactile, nociceptive, and possibly auditory components of CVS do not influence the results of the measurements, i.e., waiting for 10 s after the injection of cold water prior to the start of PET data acquisition (Bottini et al 1994(Bottini et al , 2001 or delaying the start of PET investigations by an average of 145 and 25 s following stimulation with cold water or warm air, respectively, in an effort ensure that the effect of fast-quenching activation due to mechanical and CVS is decreased (Wenzel et al 1996). In earlier experiments (Kisely et al 2001), we applied the technique of stimulation with icy water and found that this resulted in an expressed and prolonged sensation of cold and pain, which persisted during data acquisition. These observations immediately led to the question as to which of the components of the changes in rCBF induced by CVS stimulation could be attributed to the processing of vestibular signals and which were related to the pain or cold sensation.…”
Section: Discussionmentioning
confidence: 95%
“…The introduction of functional imaging into research relating to the processing of signals of the vestibular system proved to be a breakthrough (Bense et al 2001;Bottini et al 1994Bottini et al 1995Bottini et al , 2001Brandt et al 1998Brandt et al , 2002Kisely et al 2001;Lobel et al 1998Lobel et al 1999Ö dkvist et al 1974;Paulesu et al 1997;Penfield 1957;Takeda et al 1996). These techniques are suitable for studies of the regional blood flow in the CNS, which are effective in the localization of different cerebral functions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations